Long-term trends in the northern extratropical ozone laminae with focus on European stations - Laštovička, J. (Jan); Križan, P. (Peter); Kozubek, M. (Michal) (Journal of Atmospheric and Solar-Terrestrial Physics, 2014)
Narrow layers of substantially enhanced ozone concentration in ozonesonde-observed ozone profiles, called positive ozone laminae, reveal much stronger trend than the stratospheric and total ozone itself. They seem to be sensitive to both the ozone concentration and even more to changes in the stratospheric dynamics. We are studying long-term trends of strong positive laminae based on balloon-borne ozone sounding in Europe, Japan, North America and Arctic over 1970–2011 with focus on European stations due to their highest frequency of ozone sounding. Laminae characteristics exhibit strong negative trend till the mid-1990s (decrease by 50% or more). In more recent years this negative trend reverses to a positive trend. According to regression analysis, several factors play a role in the trend in laminae in Europe, namely NAO, EESC and the behavior of the winter polar stratospheric vortex represented here by the 10 hPa polar temperature. On the other hand, several factors are found not to play a significant role in the long-term trend in laminae.